Ex Vivo Evaluation of the Efficacy of Antibiotic Pastes Used as Intracanal Medication - Calderón Brenes MQC, Melissa Cristina (2015)
Clinical and research reports evidence cases of failed endodontic treatment complaining bacterial resistance to conventional therapeutic protocols. Thus, the use of an alternative intracanal medication covering a broader microbial spectrum in order to increase the success rate of endodontic treatment is necessary. In the present study the bacterial colonization of Enterococcus faecalis (ATCC 29212), Porphyromonas gingivalis (ATCC 33277), Actinomyces odontolyticus (ATCC 17929) and Prevotella bucae (LIBA-6229) on dentin specimens and in an ex vivo model simulating human root canal infection was demonstrated. Our study evaluated the antimicrobial effectiveness of two poliantibiotic pastes (amoxicillin with clavulanic acid-ciprofloxacin and metronidazole-amoxicillin-ciprofloxacin), and calcium hydroxide dressing. Both antibiotic intracanal dressings were equally effective for bacteria eradication, however in both research models, poliantibiotic pastes reveal higher antimicrobial effectiveness than calcium hydroxide.